Impact of endocardial leads on the effectiveness of interventional edge-to-edge repair of tricuspid regurgitation. (4th February 2022) - Goebel, B; Salomon, C; Abdulrahman, M; Richter, S; El Garhy, M; Costello-Boerrigter, L; Lapp, H; Lauten, P
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: A considerable proportion of patients who are considered for percutaneous tricuspid valve edge-to-edge repair (pTVR) interventions have endocardial lead induced tricuspid regurgitation (TR). The aim of this study was to examine the impact of lead-leaflet interaction on the effectiveness of pTVR. Methods: For each patient, the lead position within the tricuspid valve (central, commissural, or towards one of the three leaflets) and the type of lead-leaflet interaction (leaflet impingement or adhesion) were identified during thorough 2D/3D transthoracic and transesophageal echocardiography examinations. Before and after pTVR, echocardiographic data, including 3D full-volume datasets, were obtained and quantified. TR severity was graded from 1+ to 5+, based upon the effective regurgitant orifice area by the PISA method (EROAPISA) and the vena contracta area (VCA3D) as measured by multiplanar reconstruction from a 3D color Doppler loop. Maximal diastolic tricuspid annulus area from a 3D zoom image, tricuspid tenting area, and right atrial volume were quantified. Right ventricular assessments included ejection fraction (RVEF3D) and diastolic (RVVd3D) and systolic (RVVs3D) volumes.  Results: Out of 99 patients who underwent pTVR at our hospital, 38 patients had implanted cardiac devices of the following types: pacemakers (n = 25, 66%), cardiac defibrillators (n = 7, 18%), and biventricular pacemakers (n = 6, 16%). In 24 (63%) of these device patients, TR grade was ≤2+ after pTVR. In 14 of the device patients, TR grade remained severe after intervention (Grade 3+ in 15%, grade 4+ in 11%, and Grade 5+ in 11% of the device group). In comparison, in 78% of patients without endocardial leads, moderate TR was achieved after pTVR. Figure 1 shows the distribution of lead positions within the tricuspid valve. A relevant lead-leaflet interference (rLLI) for pTVR interventions was defined as impingement or adhesion in the target area of the coaptation device (anteroseptal or posteroseptal). Binary logistic regression analysis showed an increase risk (Odds ratio 11, R2 0.34, 95% CI 0.019-0.44, p = 0.003) for a suboptimal pTVR result (TR grade > 2+ after intervention) in patients with rLLI. Although patients with rLLI (n = 17) had significantly higher VCA3D values as compared to patients without rLLI (n = 21), it was not predictive for pTVR results. Echocardiographic parameters of right ventricular and tricuspid valve dimensions showed only a trend to higher values in the group with rLLI (Table 1). Conclusion:   Endocardial lead induced TR negatively impacts the effectiveness of pTVR irrespective of the initial degree of TR.